Performance improvement by using ammonia water-synthesized TiO2 nanotubes with nanowire porous film mixed nanostructures. Issue 31 (21st August 2015) - Lv, Pin; Fu, Wuyou; Mu, Yannan; Sun, Hairui; Liu, Tie; Wang, Jun; Niu, Jiasheng; Li, Xue; Liu, Li; Yang, Haibin
<x xml:space="preserve">Abstract</x> In this work, the morphology of TiO2 nanotubes with small nanowires directly formed on top (designated as TTW) was treated by the method of wet-chemical reaction (WCR) with an alkaline solution.